Cultural Atmosphere as a Component of the Quality of Life in Cities - Majer, Andrzej (Journal of Public Governance, 2021)
Objectives: The aim of this paper is to draw attention to the fact that cultural atmosphere or ambience – although underestimated – is one of the key aspects of the quality of life in cities. Research Design & Methods: The article is theoretical, as it reviews the literature on the quality of life and the characteristics of cities, trying to identify their main determinants as well as, against this background, to show the importance of cities’ cultural atmosphere. Findings: The author attempts to prove that the cultural atmosphere is difficult to define, yet it is important feature regarding, for example, motives for attachment to the city or to local patriotism. The paper also explores how the cultural ambience is considered as a significant factor when taking into consideration location-related decisions. Implications / Recommendations: The subject of the article belongs to the sphere equally important to that of economic features. The culture and its character, elusive yet spectacular, manifests as a vibrant presence of people leading their existence and living side by side in the common environment. Immigrants, clerks, artists, street vendors, and police officers – alongside thousands of homeless people – create spectacular mélange and the character of the city. These features have to be considered. Contribution / Value Added: This paper tries to ease the relative shortage of scientific analysis on the said topic. Article classification: conceptual paper JEL classification: A12